Emotional facial expression and tears simulation: an analysis & comparison of current approaches - Mohd. Rahim, Mohd. Shafry (Springer, 2015)
The enhancement of emotional expression of virtual human in extreme situation such as, crying or sweating required physical effect that involved fluid behavior. The aim of this research is to analyze the facial action coding system and smooth particle hydrodynamic strategies to effectively provide an efficient display in computer facial animation. This research reviews and compares two major techniques for generating extreme expression in 3D facial animation, the facial action coding system is employed to describe and create facial expressions. It breaks down facial actions into minor units known as action units (AU's). Emotion facial expressions generated are based on independent action unit's combination.